Reforma australijskiego systemu oceny wypłacalności i nadzoru zakładów ubezpieczeń - Kurek, Robert (The Australian Reform of Prudential Rules and Estimation of Insurance Companies' Solvency, 2005)
The Australian reform of prudential rules on non-life insurance was enforced in 2002. The new prudential standards are much more comprehensive and more discrimitive in adressing general insurance risk. New foundations of the reform consist of: the formulation of new rules on prudential standard liability valuation; the formulation of a new solvency margin rule ("prudential standard capital adequacy" rule); the formulation of rules on prudential standard risk management and the formulation of rules governing prudential standard reinsurance arrangements. In the new regime particular standards are intended to prevent undercapitalisation and aimed at discouraging poor management in general insurance. Besides there was carried out universal "health check" on all companies under the re-authorisation process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 242-250